2023
DOI: 10.3390/cancers15123246
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Risk Model for Personalized Screening and Prevention of Breast Cancer

Abstract: Background: Image-derived artificial intelligence (AI) risk models have shown promise in identifying high-risk women in the short term. The long-term performance of image-derived risk models expanded with clinical factors has not been investigated. Methods: We performed a case–cohort study of 8110 women aged 40–74 randomly selected from a Swedish mammography screening cohort initiated in 2010 together with 1661 incident BCs diagnosed before January 2022. The imaging-only AI risk model extracted mammographic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…42 A recent study indicated that an image-based model not only showed an overall higher discriminative performance compared to a clinical lifestyle/familial-based risk tool, but also higher discriminatory performances across subgroups of women by established risk factors of breast cancer and by breast cancer subtypes. 29 Considering the reporting from several research groups on the performance of image-based risk models, such newer approaches for identifying women in need to supplemental screening and a shorter screening interval may be considered in updated screening guidelines. 39 , 43 , 44 , 45 However, the risk-benefit balance of these models at an individual and societal level needs to be assessed before their clinical implementation for an individualized screening approach.…”
Section: Discussionmentioning
confidence: 99%
“…42 A recent study indicated that an image-based model not only showed an overall higher discriminative performance compared to a clinical lifestyle/familial-based risk tool, but also higher discriminatory performances across subgroups of women by established risk factors of breast cancer and by breast cancer subtypes. 29 Considering the reporting from several research groups on the performance of image-based risk models, such newer approaches for identifying women in need to supplemental screening and a shorter screening interval may be considered in updated screening guidelines. 39 , 43 , 44 , 45 However, the risk-benefit balance of these models at an individual and societal level needs to be assessed before their clinical implementation for an individualized screening approach.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age is 53.77 (11.79) and 56.18 (11.68) for subcohort and case groups, respectively 26,33 . The table also reports the family history of breast cancer and ovarian cancer for both groups.…”
Section: Datasets For Model Training and Evaluationmentioning
confidence: 99%
“…Our work, along with other studies, has demonstrated that incorporating the image alongside mammographic density can enhance long-term breast cancer risk prediction. [4][5][6] However, in our previous work, we relied on averaging between the pair of images after proper image registration. 4,5 As a result, there has been a lack of investigation into studying the correlated pair of images as a whole.…”
Section: Introductionmentioning
confidence: 99%